Variations in the Wnt/β-Catenin Pathway Key Genes as Predictors of Cervical Cancer Susceptibility - Wang B; Wang M; Li X; Yang M; Liu L (Pharmacogenomics and Personalized Medicine, 2020)
Bingqi Wang, Min Wang, Xianping Li, Min Yang, Lei Liu Department of Laboratory Medicine, The Second Xiangya Hospital, Central South University, Changsha 410011, Hunan, People’s Republic of ChinaCorrespondence: Min WangDepartment of Laboratory Medicine, The Second Xiangya Hospital, Central South University, 139 Middle Renmin Road, Changsha 410011, Hunan, People’s Republic of ChinaTel/Fax +86 132 9869 7558Email wangmin0000@csu.edu.cnBackground: Cervical cancer is the fourth most common and fatal tumor among women worldwide. The Wnt/β-catenin signaling pathway was etiologically involved in the cervical cancer model. Herein, we aimed to investigate whether germline genetic variations within the Wnt/β-catenin pathway can be genetic risk factors of cervical cancer.Patients and Methods: A total of 305 samples (147 patients, 158 controls) were included. Eight genetic variations located in APC (rs454886), GSK3β (rs3755557), CTNNB1 (rs11564475, rs1798802, rs3864004, rs2293303, and rs4135385), and TCF7L2 (rs7903146) were genotyped via Sanger sequencing. The χ2 test and non-conditional logistic regression were used in the single-locus analysis. Gene–gene interactions and haplotype construction in case–control samples were performed by the GMDR method and Haploview software, respectively.Results: The frequency of CTNNB1 rs1798802 GA+AA genotype was significantly lower in cervical cancer patients adjusted for age (OR=0.626, 95% CI=0.398– 0.984). The mutant alleles of rs3864004 (A) and rs2293303 (T) located in CTNNB1 showed 1.513 (1.038– 2.207), and 1.654 (1.020– 2.683) fold increased risk of cervical cancer, respectively. Haplotype analysis showed no association between haplotypes of the CTNNB1 gene and cervical cancer risk. No significant contribution of interactions among genes in the Wnt pathway was identified.Conclusion: We concluded that the genetic variants in the CTNNB1 gene might contribute to the development of cervical cancer.Keywords: cervical cancer, Wnt/β-catenin signaling pathway, single nucleotide polymorphism, APC, GSK3β, CTNNB1, TCF7L2